An efficient hybrid conjugate gradient method for unconstrained optimization. (4th July 2022) - Ibrahim, Abdulkarim Hassan; Kumam, Poom; Kamandi, Ahmad; Abubakar, Auwal Bala
Abstract : In this paper, we propose a hybrid conjugate gradient method for unconstrained optimization, obtained by a convex combination of the LS and KMD conjugate gradient parameters. A favourite property of the proposed method is that the search direction satisfies the Dai–Liao conjugacy condition and the quasi-Newton direction. In addition, this property does not depend on the line search. Under a modified strong Wolfe line search, we establish the global convergence of the method. Numerical comparison using a set of 109 unconstrained optimization test problems from the CUTEst library show that the proposed method outperforms the Liu–Storey and Hager–Zhang conjugate gradient methods.